2007
DOI: 10.1038/sj.bmt.1705868
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future perspectives for yttrium-90 (90Y)-ibritumomab tiuxetan in stem cell transplantation for non-Hodgkin's lymphoma

Abstract: Haematopoietic SCT is currently considered a therapeutic option mainly in relapsed or refractory non-Hodgkin's lymphoma (NHL) owing to high post-transplantation relapse rates and significant toxicity of conventional myeloablative conditioning for allogeneic SCT. Radiolabelled immunotherapy combines the benefits of monoclonal antibody targeting with therapeutic doses of radiation, and is a promising advance in the treatment of malignant lymphomas. It is now under investigation as a component of conditioning pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…More phase 2 and subsequent phase 3 studies are needed to evaluate the role of 90 Y-ibritumomab tiuxetan in combination with HDT (eg, Z-BEAM vs BEAM) or alone before ASCT. These studies should investigate different patient subgroups and analyze outcomes according to histology [23,24].…”
Section: New Treatment Concepts and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…More phase 2 and subsequent phase 3 studies are needed to evaluate the role of 90 Y-ibritumomab tiuxetan in combination with HDT (eg, Z-BEAM vs BEAM) or alone before ASCT. These studies should investigate different patient subgroups and analyze outcomes according to histology [23,24].…”
Section: New Treatment Concepts and Future Directionsmentioning
confidence: 99%
“…Several independent studies in the transplant setting showed that 90 Y-ibritumomab tiuxetan has a promising role in conditioning regimens, not only as an adjunct to standard chemotherapy (immunotherapyenhanced conditioning) but also as the sole conditioning agent, extending the option of transplantation to a wider range of patients [21][22][23][24][25]. In ASCT, the use of 90 Y-ibritumomab tiuxetan combined with HDT has no effect on the speed of engraftment and has a toxicity profi le similar to that of conventional conditioning regimens [22,26].…”
Section: New Treatment Concepts and Future Directionsmentioning
confidence: 99%
“…The European MCL Network trials are now comparing classical total-body irradiation (TBI) at 12 Gy plus cyclophosphamide at 120 mg/kg (CTX) with TAM (TBI, 10 Gy; cytarabine, 6 g/m 2 ; and melphalan, 140 mg/m 2 ) [23]. The high radiosensitivity of MCL, however, is now exploited in the form of radioimmunotherapy targeting CD20, with two agents presently available-yttrium 90 ( 90 Y)-ibritumomab tiuxetan (Zevalin; Cell Therapeutics, Inc., Seattle, WA) and iodine 131 ( 131 I)-tositumomab (Bexxar; GlaxoSmithKline, Philadelphia, PA, and Biogen Idec, San Diego, CA)-both with documented effi cacy in MCL (reviewed by Gisselbrecht et al [34] and Park and Press [35]). Followed by stem cell support, radioimmunotherapy as part of the preparatory regimen appears to be an effective and well-tolerated alternative to TBI [36].…”
Section: Preparatory Regimensmentioning
confidence: 99%
“…This is especially pertinent because the majority of patients with relapsed or refractory B-cell NHL are Ͼ60 years old, and yet are often denied potentially curative HDC and/or TBI and ASCT because of the risk for excessive treatmentrelated morbidity and mortality [20,21]. In contrast to TBI, and by virtue of its targeted activity, RIT (conventional and high dose) can be used in elderly patients with comorbidities undergoing SCT, making it appropriate as a pretransplant regimen for a wider patient population [19]; as such, a dramatic decrease in TBI-containing regimens has been observed in data from the European Group for Blood and Marrow Transplantation registry since 2000 [22,23]. In two studies, 90 Yibritumomab tiuxetan was used to treat patients with NHL who were not eligible for HDC-and/or TBI-containing therapies prior to ASCT.…”
Section: The Role Of Radioimmunotherapy As a Pretransplant Conditionimentioning
confidence: 99%